A Thematic Review of Tablet-Based Science Education Studies - Ummuhan Ormanci; Salih Cepni (Journal of Education in Science, Environment and Health)
The use of tablet in schools has been getting importance in a parallel with any change in educational policies. It can be said that the use of tablets was investigated on the variables such as success and attitude in the literature and the number of studies increased related to the applications that can be used in tablets. In this context, it was considered that analyzing the studies conducted in the field of science education, which was one of the courses where tablet use was recommended, will be important for both teacher - prospective teacher candidates who were practitioner and literature. The aim of this study was to thematically examine and analyze tablet-based science education studies. 25 articles were exposed to this thematic review via the matrix developed by Ormanci et al. (2015). The matrix consists of two parts-general properties (type of journals, years, etc.) and content (rationales, aims, research methods, etc.). The results indicated rationales of related studies were very limited. Further, there were experimental studies examining the effects of tablet-based science education on student success and performance. None of previous studies examined the effects of tablet-based science education on the participants‟ skills, which should be investigated in future studies.